2009
DOI: 10.1182/blood-2008-01-136879
|View full text |Cite
|
Sign up to set email alerts
|

Both alleles of PSF1 are required for maintenance of pool size of immature hematopoietic cells and acute bone marrow regeneration

Abstract: Hematopoietic stem cells (HSCs) have a very low rate of cell division in the steady state; however, under conditions of hematopoietic stress, these cells can begin to proliferate at high rates, differentiate into mature hematopoietic cells, and rapidly reconstitute ablated bone marrow (BM). Previously, we isolated a novel evolutionarily conserved DNA replication factor, PSF1 (partner of SLD5-1), from an HSCspecific cDNA library. In the steady state,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 33 publications
3
47
0
Order By: Relevance
“…The molecular basis of the HSC response to the chemotherapeutic drug 5-FU involves activation of proliferation and modification of adhesion [11]. In addition, the evolutionarily conserved DNA replication factor PSF1, is required for regeneration after 5-FU treatment and to maintain HSC numbers [55].…”
Section: Injury -How Do Hscs React?mentioning
confidence: 99%
“…The molecular basis of the HSC response to the chemotherapeutic drug 5-FU involves activation of proliferation and modification of adhesion [11]. In addition, the evolutionarily conserved DNA replication factor PSF1, is required for regeneration after 5-FU treatment and to maintain HSC numbers [55].…”
Section: Injury -How Do Hscs React?mentioning
confidence: 99%
“…Quantitative reverse transcription-PCR (RT-PCR) was done as previously described (14). The primer sets were described in Supplementary Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…For immunocytochemistry, anti-PSF1(14), anti-bromodeoxyuridine (BrdUrd) (Zymed Laboratories), anti-β-tubulin (Sigma), anti-CENP-A (MBL), and anti-survivin (Chemicon International, Inc.) antibodies were used as previously described (14).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PSF1 is a member of the GINS (Go-IchiNi-San) complex associated with the formation of the DNA replication fork. We found that PSF1 is required for acute proliferation of normal stem cells such as epiblasts in the embryo and hematopoietic stem cells in bone marrow [17,18]. PSF1 expression visualized by enhanced green fluorescent protein (EGFP) under the transcriptional control of the PSF1 promoter in lung cancer cells (LLC-PSF1p-EGFP cells) indicated that a high level of PSF1 transcriptional activity in cancer cells (PSF1-EGFP high ) derived from tumors in vivo was associated with a higher invasive, tumorigenic, and metastatic activity compared with PSF1-EGFP low cancer cells.…”
Section: Introductionmentioning
confidence: 99%